Comparison of incidence and cost of influenza between healthy and high-risk children <60 months old in Thailand, 2011-2015 - Kittikraisak, Wanitchaya; Suntarattiwong, Piyarat; Kanjanapattanakul, Wiboon; Ditsungnoen, Darunee; Klungthong, Chonticha; Lindblade, Kim A.; Fernandez, Stefan; Dawood, Fatimah S.; Chotpitayasunondh, Tawee; Olsen, Sonja J. (PloS one, 2018)
Thailand recommends influenza vaccination for children aged 6 months to <36 months, but investment in vaccine purchase is limited. To inform policy decision with respect to influenza disease burden and associated cost in young children and to support the continued inclusion of children as the recommended group for influenza vaccination, we conducted a prospective cohort study of children in Bangkok hospital to estimate and compare influenza incidence and cost between healthy and high-risk children. Caregivers of healthy children and children with medical conditions ('high-risk') aged <36 months were called weekly for two years to identify acute respiratory illness (ARI) episodes and collect illness-associated costs. Children with ARI were tested for influenza viruses by polymerase chain reaction. Illnesses were categorized as mild or severe depending on whether children were hospitalized. Population-averaged Poisson models were used to compare influenza incidence by risk group. Quantile regression was used to examine differences in the median illness expenses. During August 2011-September 2015, 659 healthy and 490 high-risk children were enrolled; median age was 10 months. Incidence of mild influenza-associated ARI was higher among healthy than high-risk children (incidence rate ratio [IRR]: 1.67; 95% confidence interval [CI]: 1.13-2.48). Incidence of severe influenza-associated ARI did not differ (IRR: 0.40; 95% CI: 0.11-1.38). The median cost per mild influenza-associated ARI episode was $22 among healthy and $25 among high-risk children (3-4% of monthly household income; difference in medians: -$1; 95% CI for difference in medians: -$9 to $6). The median cost per severe influenza-associated ARI episode was $232 among healthy and $318 among high-risk children (26-40% and 36-54% of monthly household income, respectively; difference in medians: 110; 95% CI for difference in medians: -$352 to $571). Compared to high-risk children, healthy children had higher incidence of mild influenza-associated ARI but not severe influenza-associated ARI. Costs of severe influenza-associated ARI were substantial. These findings support the benefit of annual influenza vaccination in reducing the burden of influenza and associated cost in young children.